Lake phytoplankton status and trends: a case study from Greek lakes, Eastern Mediterranean (2025)
Nikolopoulou, I., E. Mavromati, K. Moschandreou, V. Navrozidou, D. Kemitzoglou, and V. Tsiaoussi. 2025. Lake phytoplankton status and trends: a case study from Greek lakes, Eastern Mediterranean. Environmental Monitoring Assessment 197: 733. https://doi.org/10.1007/s10661-025-14147-7.